2009
DOI: 10.1002/ccd.22287
|View full text |Cite
|
Sign up to set email alerts
|

Indications and clinical outcomes for below knee endovascular therapy: Review article

Abstract: Chronic critical limb ischemia (CLI) still represents the most common cause for amputation and frequently the possibility for peripheral revascularization, particularly in below knee (BK) arteries, is not adequately evaluated before amputation. This may also be due to the fact that even today, there's some confusion about results of the endovascular treatment in this territory. Diabetics, representing the population most frequently affected by CLI, have specific clinical characteristics, the so called diabetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 30 publications
4
41
0
6
Order By: Relevance
“…Кроме того, рекомендуется частое динамическое наблюдение пациентов после эндоваскулярного лечения, особенно в случае неблагоприятных исходов реваскуляри-зации и гемодинамически значимых осложнений целевых артерий, выявленных в раннем периоде наблюдения [36]. Стратегия эндоваскулярного лечения КИНК у пациентов с СД и у лиц без нарушения углеводного обмена представ-лена в таблице 2 [7].…”
Section: особенности эндоваскулярного лечения больных сд и кинкunclassified
See 2 more Smart Citations
“…Кроме того, рекомендуется частое динамическое наблюдение пациентов после эндоваскулярного лечения, особенно в случае неблагоприятных исходов реваскуляри-зации и гемодинамически значимых осложнений целевых артерий, выявленных в раннем периоде наблюдения [36]. Стратегия эндоваскулярного лечения КИНК у пациентов с СД и у лиц без нарушения углеводного обмена представ-лена в таблице 2 [7].…”
Section: особенности эндоваскулярного лечения больных сд и кинкunclassified
“…Основные показатели оценки эффективности рева-скуляризации конечности и дальнейшей тактики веде-ния больных СД представлены в таблице 3 [7].…”
Section: © сахарный диабет 2015unclassified
See 1 more Smart Citation
“…25 Recanalization of total occlusions is usually associated with lower technical success rates. The introduction of flexible low-profiles balloons in longer lengths (up to 210 mm) has facilitated BTK angioplasty procedures, improving procedure time and potentially reducing dissections in long segments of diffuse disease (Figure 4).…”
Section: Dedicated Btk Balloon Angioplastymentioning
confidence: 99%
“…The primary goal of PTA treatment is to restore the patency of at least one below-the-knee (BTK) vessel, preferably the tributary of the anatomical region of the ulcer [9]. Several studies have demonstrated good results in terms of patency and limb salvage after endovascular treatment of diabetic foot [10][11][12][13][14]. Many, however, are limited by the presence of a heterogeneous population with different stages of ischemia (claudication, rest pain, trophic lesions) and different treatment modalities, with PTA performed both in the above-the-knee (ATK) and BTK areas [15][16][17].…”
Section: Introductionmentioning
confidence: 99%